1997
DOI: 10.1172/jci119364
|View full text |Cite
|
Sign up to set email alerts
|

Tyrphostin AG 556 improves survival and reduces multiorgan failure in canine Escherichia coli peritonitis.

Abstract: Tyrosine kinase-dependent cell signaling is postulated to be a pivotal control point in inflammatory responses initiated by bacterial products and TNF. Using a canine model of gram-negative septic shock, we investigated the effect of tyrosine kinase inhibitors (tyrphostins) on survival. Animals were infected intraperitoneally with Escherichia coli 0111: B4, and then, in a randomized, blinded fashion, were treated immediately with one of two tyrphostins, AG 556 ( n ϭ 40) or AG 126 ( n ϭ 10), or with control ( n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 37 publications
2
20
0
Order By: Relevance
“…Furthermore, treatment of the animals 1 h after induction of meningitis still inhibited the increase in rCBF. This is consistent with significantly improved hemodynamic parameters seen in tyrphostintreated animals with multiorgan failure caused by Escherichia coli (26).…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, treatment of the animals 1 h after induction of meningitis still inhibited the increase in rCBF. This is consistent with significantly improved hemodynamic parameters seen in tyrphostintreated animals with multiorgan failure caused by Escherichia coli (26).…”
Section: Discussionsupporting
confidence: 85%
“…Fink et al implanted a fibrin clot containing live E. coli in the peritoneal cavity of dogs, which increased cardiac output and decreased blood pressure and systemic vascular resistance (SVR) (85). This canine sepsis model has been used for drug evaluation (86)(87)(88)(89). Recently a new canine sepsis model induced by intrabronchial Staphylococcus aureus administration has been developed (90).…”
Section: Large Animal Models and Bacterial Infusion/inoculationmentioning
confidence: 99%
“…In the lung, the positive effects of AG126 and AG556 have been attributed to the suppressed iNOS and COX-2 protein expression and activity. AG126 and AG556 have been studied in canine Escherichia coli sepsis also 19 . While AG556 significantly lowered the serum TNF levels, thus preventing cytokine-induced multiorgan failure and death, AG126 on whole, did not show such therapeutic effect in this model.…”
Section: Tyrphostins In Sepsis Modelsmentioning
confidence: 99%
“…Later, a broad spectrum of biological activities have been added like antioxidant, increase of cellular glutathione level, suppression of poly ADP (adenosine diphosphate)-ribose polymerase (PARP) activation 11 , as well as these compounds potentiate the expression of some redox-sensitive genes associated to mitogen-activated protein kinase (MAPK), AP-1 and Nrf2 factors 12,13 . TYK inhibitors, except being broadly used in cancer clinical trials 14 , have also been evaluated in animal models of type 1 diabetes 15,16 , multiple sclerosis 17 , intestinal inflammation 18 and septic shock 19 . A number of studies have shown that in general tyrphostins express their anti-inflammatory activity by modulation of pro-inflammatory gene expression, such as cyclooxygenase-2 (COX2), inducible nitric oxide synthase (iNOS) and several pivotal cytokines ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%